Chivalrous Chemistry. (3rd July 2019) - Lloyd Edmondson, Hattie
Abstract : In Science as Public Culture (1992), Jan Golinski argued that Humphry Davy's career was "substantially responsible" for allowing chemistry to emerge "with greatly enhanced esteem and respectability" from the "crisis" of the 1790s, when it had become associated with the radical politics of the chemists Joseph Priestley (1733–1804) and Thomas Beddoes (1760–1808). In this paper, I will flesh out the transformation noted by Golinski of chemistry into a respectable discipline under Davy's tenure at the Royal Institution. The dissociation of chemistry from radical politics was achieved through the influence of Davy's upper-class, female-audience at the Institution. Davy's audience wanted chivalry, therefore Davy made his chemistry chivalrous. To borrow from Samuel Taylor Coleridge's (1772–1834) assessment of his friend in 1804, Davy was "more and more determined to mould himself upon the age in order to make the age mould itself upon him."